Sin importar el tamaño todos somos humanos - Sánchez Marles, Luz Angélica (Universidad de San Buenaventura - Cali, 2018)
This project of degree evidences the social look that one has in front of the people who suffer from achondroplasia, from the development of these subjects in their family, cultural and educational environment. All this is carried out through a documentary research that allows to achieve the objective of categorizing and analyzing some documentary sources such as: research carried out by some authors, informative documents, audiovisual productions, stories, legislative acts, documents, institutions and records in networks social, which managed to contribute to the identification of the relationship between the body and education, highlighting social strategies already implemented in several countries that managed to strengthen the training of these subjects changing in some way or another the cultural perspective that you have of these people.